Toll-Like Receptor-1 Single-Nucleotide Polymorphism 1805T/G Is Associated With Predisposition to Multibacillary Tuberculosis - Barletta-Naveca, Raphaela Honorato; Naveca, Felipe Gomes; Almeida, Vanessa Alves de; Porto, Jorge Ivan Rebelo; Silva, George Allan Villarouco da; Ogusku, Mauricio Morishi; Sadahiro, Aya; Ramasawmy, Rajendranath; Boechat, Antonio Luiz (Frontiers in Immunology, 2018)
Tuberculosis (TB), caused by mycobacterial species of the Mycobacterium tuberculosis complex, is a serious global health issue. Brazil is among the 22 countries with the highest number of TB cases, and the state of Amazonas has the highest incidence of TB cases in the country. Toll-like Receptors (TLRs) are important pattern recognition receptors of the innate immunity and play a key role in orchestrating an effective immune response. We investigated whether the single-nucleotide polymorphisms (SNPs) 1805 T/G TLR1, 2258 G/A TLR2, 896A/G and 1196C/T of TLR4, 745T/C TLR6 and -1237A/G and -1486A/G of TLR9 are associated with the predisposition to TB and/or bacillary load. The SNPs genotyping was performed by nucleotide sequencing in 263 TB patients and 232 healthy controls residing in the state of Amazonas. Alleles and genotypes frequencies were similar between patients and healthy individuals for most of the investigated SNPs. Stratification of the TB patients according to their bacillary load showed that the genotype 1805TT TLR1 (rs5743618) was prevalent among paucibacillary patients (OR = 0.38; 95% CI = 0.19-0.76; p = 0.009) while the genotype 1805TG was common among multibacillary patients (OR: 3.72 CI: 1.65-8.4 p = 0.004). Comparison of demographic characteristics of patients to controls showed that TB is strongly associated with smoking (OR = 6.55, 95% CI = 3.2-13.6; p < 0.0001); alcohol use disorder (AUD) (OR = 7.14, 95% CI = 3.7-13.9; p < 0.0001) and male gender (OR = 3.66; 95% CI = 2.52-5.3; p < 0.0001). Multivariate logistic regression demonstrated that alcoholism (OR = 2.93, 95% CI = 1.05-8.16, p = 0.03) and the1805G allele (OR = 2.75, 95% CI = 1.33-5.7; p = 0.006) are predictive variables for multibacillary TB. Altogether, we suggest that the TLR1 1805G allele may be a relevant immunogenetic factor for the epidemiology of TB together with environmental, sociodemographic and behavioral factors.